Relationship between Scientific Attitude and Student Learning Outcomes In the Microbiology Course - Efgivia, M. Givi; Sumarmi, Sumarmi; Suciana, Ewin (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
One of the educational problems faced by Indonesia is the low critical thinking skills of students. The purpose of this study was to determine the relationship between scientific attitudes and student learning outcomes (critical thinking) in the Microbiology course. The method used in this research is correlation. The sample in this study were 28 students. Analysis of the data used in this study using the Kolmogorov-Smirnov data normality test and the Pearson product moment correlation test. The results of this study indicate a relationship between scientific attitudes and learning outcomes which can be seen from the sig value. equal to 0, 343. Meanwhile, the relationship between scientific attitudes and learning outcomes is 46.3%.